Pengaruh Variasi Holding Time pada Proses Single Stage Aging Terhadap Kekerasan dan Mikrostruktur pada Material Paduan Al-Si-Cu-Fe - Shieddieque, Apang Djafar; Kuswandi, Rendi (Universitas Trunojoyo Madura, 2025)
The Al-Si-Cu aluminum alloy is the most commonly used alloy for household appliances, aircraft materials, automotive, marine vessels, construction, and more. However, cast aluminum alloys still exhibit low mechanical properties, necessitating additional processes to enhance their strength. One method of strengthening aluminum is by varying the composition and/or heat treatment process. The aim of this research is to investigate the effect of aging time variation on the microstructure and hardness of the Al-Si-Cu-Fe alloy. The heat treatment processes conducted in this study include solid solution treatment (T=540°C and t=5 hours) and various single-stage aging treatments (T=155°C and t=4, 5, and 6 hours). Mechanical properties of the aluminum alloy were evaluated through metallographic observations and Brinell hardness testing. Microstructural observations indicate changes in the Silicon microstructure from the As cast sample, which exhibits dendrites, to the formation of AlSi and AlFeSi phases after aging treatment. With longer aging treatments, larger and more dispersed precipitate grains are formed. The variation in holding time has different effects on hardness, with the highest hardness obtained at a holding time of 4 hours during artificial aging, resulting in 71.57 BHN. However, increasing the holding time tends to decrease hardness due to the growth of larger precipitate phases.